2023
DOI: 10.1680/jcoma.19.00053
|View full text |Cite
|
Sign up to set email alerts
|

Pelletisation factors on the production of fly-ash aggregates and its performance in concrete

Abstract: This research study investigates the factors associated with pelletisation in the production of fly-ash aggregates and its performance in concrete. To investigate this influence, experiments were carried out in different stages to explore the effect of factors responsible for pelletisation, which were designed through Taguchi's experimental design. Additionally, the influence of each parameter on the engineering properties of the produced aggregates was determined using Grey relational analysis. Further, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In this research, three types of curing were adopted to develop GPC. The first type of curing was oven curing, specimens GPC-NO and GPC-RO under this category were heated to a temperature of 60°C for 24 h (Rangan, 2008; Hardjito et al , 2004; Ahmed et al , 2020; Shivaprasad et al , 2019; Anuradha et al , 2012; Noushini et al , 2015). They developed a dense and compact alumino-silicate gel and a better interfacial transition zone between the binder and the filler as proved by the SEM examination of GPC specimens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research, three types of curing were adopted to develop GPC. The first type of curing was oven curing, specimens GPC-NO and GPC-RO under this category were heated to a temperature of 60°C for 24 h (Rangan, 2008; Hardjito et al , 2004; Ahmed et al , 2020; Shivaprasad et al , 2019; Anuradha et al , 2012; Noushini et al , 2015). They developed a dense and compact alumino-silicate gel and a better interfacial transition zone between the binder and the filler as proved by the SEM examination of GPC specimens.…”
Section: Resultsmentioning
confidence: 99%
“…It is recommended to add the SS with SH after the liberation of heat. The alkaline solution was prepared 24 h (Shivaprasad, 2019) before casting of specimens to initiate the polymerization chain reaction (Vijaya Rangan, 2014). The alkaline liquid to FA ratio was considered as 0.61, and the alkali-hydroxide to silicate solution ratio was 1:2.5 to develop appropriate GPC mixtures (Anuradha et al , 2012; Noushini et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shivaprasad et al [34] reported the production of factory-made aggregates using a granulator of diameter 500 mm and depth 125 mm. The disk rotation speed was varied from 1 to 55 rpm, and the tilt angle was varied from 0 to 70°.…”
Section: Introductionmentioning
confidence: 99%
“…But now, the usage of this technique is gaining importance recently to overcome the shortage of aggregates in meeting the demand of aggregates. Research on the manufacture of artificial aggregates utilizing the by-products from the industry like fly ash, bottom ash etc by agglomeration technique is studied [3]. Artificial aggregates can be produced by clustering fly ash into lumps in a pelletizer and then adopting hardening methods such as sintering, cold bonding, water curing, autoclaving and steam curing [4].…”
Section: Introductionmentioning
confidence: 99%